2012
DOI: 10.1007/s12603-012-0429-x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term maintenance of weight loss after lifestyle intervention in frail, obese older adults

Abstract: Objectives-To determine if long-term weight loss with associated improvement in physical and metabolic health can be maintained after lifestyle intervention in frail, obese older adults.Design-Thirty-month follow-up pilot study of a 1-year lifestyle intervention trial. Setting-CommunityParticipants-Sixteen frail, obese (body mass index = 36±2 kg/m 2 ) older (71±1 yr) adults Measurements-Body weight and composition, physical function, markers of the metabolic syndrome, glucose and insulin response to an oral gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
18
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 24 publications
3
18
0
Order By: Relevance
“…Overall, WL success reported in this trial is encouraging; with 84% of participants in the PA 1 WL group weighing less at 18 months than at baseline and sustaining an average WL of 7.7%. Long-term WL maintenance of this magnitude is in general agreement with the pilot study findings in frail, obese, older adults reported by Waters et al (16) and notably, is clinically meaningful (19). Nevertheless, we observed considerable variability about this average WL estimate (SD 5 6.8%), with 30% of participants in the PA 1 WL group experiencing weight regain of at least 2 kg during the 12-month "weight maintenance" period.…”
Section: Discussionsupporting
confidence: 92%
“…Overall, WL success reported in this trial is encouraging; with 84% of participants in the PA 1 WL group weighing less at 18 months than at baseline and sustaining an average WL of 7.7%. Long-term WL maintenance of this magnitude is in general agreement with the pilot study findings in frail, obese, older adults reported by Waters et al (16) and notably, is clinically meaningful (19). Nevertheless, we observed considerable variability about this average WL estimate (SD 5 6.8%), with 30% of participants in the PA 1 WL group experiencing weight regain of at least 2 kg during the 12-month "weight maintenance" period.…”
Section: Discussionsupporting
confidence: 92%
“…24,26 Virtually no trials have included a postintervention follow-up of 1 year or longer, which has been suggested as the optimal length of time for the evaluation of maintenance of behavioral change. 24,25 Direct comparisons of our results and the results of other trials of PA for cancer survivors are difficult because few trials have been of long-term duration or have examined long-term maintenance of PA. 23 Consistent with our findings, 2 long-term trials in breast and prostate cancer survivors reported maintenance of PA by a proportion of the intervention group. 27,28 In a study of breast cancer survivors (n 5 44) assigned to a 1-year intervention of resistance and impact training, 56% continued to exercise during the 1year follow-up; however, 43% of those who continued to exercise did so at a reduced effort.…”
Section: Discussionsupporting
confidence: 91%
“…Although rare, similar findings have been reported among older frail adults after a lifestyle intervention. 23 Furthermore, the trajectory patterns of the W/L-INT group during the second year of the observation period demonstrated that a large portion of the group (groups 2 and 3; 91.1% of the sample) increased PA upon receiving the intervention despite a 1-year waiting period.…”
Section: Discussionmentioning
confidence: 93%
“…An important limitation to improve the physical and metabolic function of older adults with obesity with weight loss therapy is reduction of BMD, which could increase the risk of fractures. (2,7,8,20) In fact, it has been reported that after long-term weight loss, bone loss continues despite some degree of weight regain (21,22) arguing against the notion that the loss of BMD with weight loss is a physiologic response to loss of total body mass. With weight regain, there is fat regain, but this is not accompanied by bone regain.…”
Section: Discussionmentioning
confidence: 99%
“…With weight regain, there is fat regain, but this is not accompanied by bone regain. (21,22) This bone loss on top of ongoing age-related bone loss may result in osteoporosis, especially among those who have lower BMD at the start of weight loss. In addition, although obesity is associated with increased BMD, it is associated with increased risk for frailty, (17,23) an independent risk factor for falls and fractures.…”
Section: Discussionmentioning
confidence: 99%